(4t)^-2 t^0/t^6 v^-8 =
[(4t)^-2][t^0/t^6][v^-8] =
[(1/16)(t^-2)][(v^-8)/t^6] =
(1/16)(t^-8)(v^-8) =
Since t^0 = 1 AND Assuming that the
But...Your notation is unclear.
You may also write:
(4t)^-2 t^0/t^6 v^-8 =
[(4t)^-2](t^0)/(t^6 v^-8) =
[(1/16)(t^-2)][(v^+8)/t^6] =
(1/16)(t^-8)(v^+8)
Check how the terms are supposed to be associated.
I previously made a mistake by leaving out an exponent from this expression;Steve wisely pointed out the error.Thank you. Will you please simplify the corrected problem.
(4t)^-2 t^0/t^6 v^-8
Thank you so much.I'll be more careful in the future.
2 answers
Actually, besides pointing out the error, I suggested a couple of things for you to use in working the problem. Too bad you didn't make the effort...